Esthetic perception and economic value of orthodontic appliances by lay Brazilian adults - Daniela Feu; Fernanda Catharino; Candice Belchior Duplat; Jonas Capelli Junior (Dental Press Editora, 2012)
OBJECTIVE: To evaluate the esthetic perception of different appliances by Brazilian lay adults and its influence in the attributed value of orthodontic treatment, considering evaluators' socioeconomic status, age and gender. METHODS: Eight different combinations of orthodontic appliances and clear tray aligners were placed in a consenting adult with pleasing smile. Standardized frontal photographs were captured and incorporated into a research album. A sample of adults (n = 252, median = 26 years old) were asked to rate each image for (1) its attractiveness on a visual analog scale and (2) the willingness to pay (WTP) for a cosmetic appliance when compared to a standard metalic appliance and a clear tray aligner. Comparisons between the appliances' attractiveness were performed using the Friedman's test and Dann's post-hoc test. Correlation between appliances' attributed value, socioeconomic status, age, gender, and esthetic perception was assessed using Spearman's correlation analysis. RESULTS: Attractiveness ratings of orthodontic appliances varied significantly in the following hierarchy: Clear aligners>sapphire brackets>self-ligating/conventional stainless steel brackets>and golden metal appliances. The correlation between WTP and esthetic perception was week. However, for individuals with better socioeconomic status and aged between 17-26 years old significantly, a significantly higher WTP was found. CONCLUSION: Clear aligners and sapphire brackets with esthetic archwire were considered better esthetic options in this sample. Nevertheless, patients were not willing to pay more money for appliances they deemed more esthetic, however, they were significantly influenced by their socioeconomic level and age. OBJETIVO: avaliar a percepção de brasileiros adultos leigos para diferentes aparelhos ortodônticos e sua influência na valorização econômica do tratamento, considerando o nível socioeconômico, idade e sexo dos avaliadores. MÉTODOS: oito combinações de aparelhos ortodônticos e alinhadores foram colocadas em um adulto com bom alinhamento dentário, e fotografias frontais foram feitas para compor um álbum de imagens de pesquisa. Uma amostra de adultos (n = 252, mediana = 26 anos) classificou cada imagem por (1) atratividade, em uma escala visual analógica, e (2) disposição a pagar a mais para realizar o tratamento com um aparelho estético em relação a um aparelho metálico e em relação a um alinhador. Comparações da atratividade dos aparelhos foram realizadas utilizando-se o teste de Friedman e o post-hoc de Dann. A correlação entre a valorização econômica, nível socioeconômico, idade, sexo e percepção estética foi calculada com a análise de correlação de Spearman. RESULTADOS: a atratividade dos aparelhos ortodônticos variou significativamente, na seguinte hierarquia: alinhadores > aparelhos de safira > aparelhos metálicos tradicionais e autoligáveis > aparelhos dourados. A correlação entre a atratividade dos aparelhos e a disposição em pagar mais por eles foi fraca. Contudo, ter melhor nível socioeconômico e idade entre 17 e 26 anos aumentou significativamente a disposição de pagar dos avaliadores. CONCLUSÕES: alinhadores e braquetes de safira com fio estético foram considerados as opções de maior atratividade para essa amostra. Entretanto, os avaliadores não estiveram dispostos a pagar a mais para realizar seus tratamentos com os dispositivos que julgaram mais estéticos, sendo, contudo, significativamente influenciados por seu nível socioeconômico e idade.